1962
DOI: 10.1080/00021369.1962.10858031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein and Energy Levels on the Growth Rate, Feed Efficiency and Carcass Composition of Chicks

Abstract: Feeding day-old \Vhite Leghorn male chicks 9 different diets for 4 weeks with the orthogonal composite design, we studied the relationship among dietary protein, energy levels and chick's responses.The ellipsoid relationship has been found fitted to describe the relationship between dietary composition and weight gain or feed efficiency of chicks, whereas declined planes are fitted to show the relationship between dietary composition and carcass protein or fat levels of chicks. Dietary protein level has great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Further, the J test has demonstrated that the improvement in the R 2 value due to the addition of the protein to energy ratio term is very low when the energy and protein levels are already in the models. The significant coefficients for energy and protein levels in the growth and feed intake prediction models show that both nutrients affect the body weight and feed intake responses (Yoshida et al, 1962;Pesti and Smith, 1984;Pesti et al, 1986). Although not all terms of the models were significantly different from zero, most experiments showed linear and or quadratic diminishing responses to energy and or protein levels.…”
Section: Discussionmentioning
confidence: 90%
“…Further, the J test has demonstrated that the improvement in the R 2 value due to the addition of the protein to energy ratio term is very low when the energy and protein levels are already in the models. The significant coefficients for energy and protein levels in the growth and feed intake prediction models show that both nutrients affect the body weight and feed intake responses (Yoshida et al, 1962;Pesti and Smith, 1984;Pesti et al, 1986). Although not all terms of the models were significantly different from zero, most experiments showed linear and or quadratic diminishing responses to energy and or protein levels.…”
Section: Discussionmentioning
confidence: 90%
“…That Summers et al (1964) failed to consistently improve protein utilization (NPU) at deficient dietary levels of protein (i.e., 10or 14%from methionine-supplemented soybean meal) when caloric density was increased probably indicates that at these protein levels, dietary energy concentration was not limiting the rate of tissue protein synthesis. Other workers who have noted increased protein utilization upon adding fat to the diet, did so in all likelihood because the basal diet to which fat was added was deficient in energy for the protein level being fed (Combs, 1964;Yoshida et al, 1962;Rand etal., 1958;Forbes and Yohe, 1955). Indeed, between metabolizable energy concentrations of 3.05 kcal./g.…”
Section: Error Mean Squarementioning
confidence: 94%
“…Dietary levels of protein and energy affected carcass fat independently over the levels employed. Research by Yoshida et al (1962) has demonstrated that the feeding of low energy-high protein diets acts to reduce the amount of carcass fat in the chicken. Kubena et al (1972) demonstrated that the amount of fat in chicken could be influenced by the feeding of isocaloric diets calculated to contain 80 to 110% of the values recommended by Combs (1970) for total sulfur amino acids.…”
Section: Introductionmentioning
confidence: 98%